Nocturnal hawkmoth and noctuid moth pollination of Habenaria limprichtii (Orchidaceae) in sub-alpine meadows of the Yulong Snow Mountain (Yunnan, China). (14th June 2018) - Tao, Zhi-Bin; Ren, Zong-Xin; Bernhardt, Peter; Wang, Wei-Jia; Liang, Huan; Li, Hai-Dong; Wang, Hong
Abstract: Habenaria (Orchidaceae) is a species-rich genus, usually pollinated by members of Lepidoptera, but the pollination ecology of its sub-alpine species in the Himalayas remains under-explored. We focused on three populations of the endangered, nectar-secreting H. limprichtii on Yulong Snow Mountain (eastern Himalayas). Results showed that spurs of H. limprichtii contained 10.8 μl of nectar with 26.3% dissolved sugars at night. A hawkmoth ( Deilephila elpenor subsp. lewisii ) and two species of settling moths ( Cucullia fraterna and Trichoplusia intermixta ) were the dominant pollinators. The hawkmoths had long proboscides (26.3 mm in length), matching the spur length of the flowers, and carried one to 30 pollinaria on their eyes. In contrast, settling moths had short proboscides (15–16.4 mm) carrying fewer than nine pollinaria on their legs or thoraces. These insects may have been attracted by the floral scent dominated by two aromatic benzenoid compounds. Flowers are self-compatible, but pollinators were required to produce fruits. Hand-pollination experiments showed a high level of inbreeding depression (a low proportion of seeds with well-developed embryos in self-pollinated fruits), whereas insect-mediated (natural) rates of cross-pollination were also low (13%). This suggests that most fruits were fertilized following moth-mediated autogamy/geitonogamy. Fruit set was always higher than the rate of pollinaria removal, suggesting a higher pollination efficiency due to its sectile and friable pollinia. Fruit set in natural populations was highly variable among years (28.5–93.7%), doubling in 2016. Although this is only the fourth case of moth-pollination described in Chinese Habenaria spp., it highlights the potential importance of this syndrome at higher elevations.